Morpheus – Remote access to micro data with a quality measure - Jörg Höhne; Julia Höninger (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2012)
Morpheus is a novel approach in providing remote access to micro data of official statistics. Researchers work on anonymous micro data files with common statistical software packages and get their results back in real time. Additionally, a measure of goodness of fit will be provided for every single result. Therefore researchers can work with the anonymous results as they can have confidence that they would have obtained the same or very similar results with the original data. All statistical analyses and all commands are allowed. Furthermore, users can browse through the anonymous data which is very helpful when developing program syntax and not possible in most other systems of remote access. Research data centres would greatly benefit from such a system as well, as the cumbersome manual disclosure control would be eliminated. All results would be safe and automatically returned to the researcher. This system would respect the special requirements to micro data access even in Germany where laws are especially strict. – – Morpheus ist ein neuartiger Ansatz, einen echten Fernzugriff auf Mikrodaten der amtlichen Statistik zu gewähren. Wissenschaftler werten mit den üblichen Statistik-Softwarepaketen einen anonymen Datensatz aus und erhalten ihre Ergebnisse in Echtzeit zurück. Zusätzlich erhalten sie zu jedem einzelnen Ergebnis ein Gütemaß. Obwohl die Wissenschaftler mit den anonymen Ergebnissen arbeiten, können sie dadurch sicher sein, dass sie das gleiche oder ein sehr ähnliches Ergebnis mit den Originaldaten erhalten hätten. Alle statistischen Analysen sind erlaubt. Darüber hinaus können sich die Wissenschaftler d ie anonymen Daten anschauen. Dies ist sehr hilfreich, wenn man Programme entwickelt und es ist in den meisten anderen Remote-Access-Systemen bisher nicht möglich. Forschungsdatenzentren würden von solch einem System ebenfalls in großem Maße profitieren, da die mühsame manuelle Geheimhaltungsprüfung entfallen würde. Alle Ergebnisse wären sicher und werden automatisch dem Wissenschaftler zugesandt. Dieses System würde die strengen gesetzlichen Datenschutzvorgaben für den Zugang zu Mikrodaten in Deutschland erfüllen.
Keywords: 330